2011
DOI: 10.1017/s1751731110002569
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a natural dietary extract, titrated in phenylpropanoid glycosides, on blood parameters and plasma oxidative status in intensively reared Italian hares (Lepus corsicanus)

Abstract: Two different doses of a natural extract titrated in phenylpropanoid glycosides (PPGs) were evaluated for their effect on blood parameters and plasma oxidative status in pairs of intensively reared Italian hares. The study lasted 210 days, during which 45 couples of hares were divided into three homogeneous groups. A control group (CON) was fed a control diet while the two experimental groups were fed a diet supplemented with 1 or 2 kg/t of a supplement titrated in PPGs. Blood samples were obtained at 0, 70, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
22
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 27 publications
9
22
1
1
Order By: Relevance
“…In the present study, dietary supplementation with VB resulted in an improvement in the plasma oxidative status as observed in our earlier works (Casamassima et al, , 2012Palazzo et al, 2011). This result might be attributed to the ability of polyphenols to neutralize free-radical production at the stage of propagation of the chain reaction (Funes et al, 2009) or to inhibit the activity of prooxidant enzymes responsible for their production, thus protecting both LDL lipids and the α-tocopherol of LDL from the attack of radicals (Cos et al, 2002), and promoting regeneration of the radical forms of α-tocopherol (Zhou et al, 2005).…”
Section: Blood Parameterssupporting
confidence: 88%
See 3 more Smart Citations
“…In the present study, dietary supplementation with VB resulted in an improvement in the plasma oxidative status as observed in our earlier works (Casamassima et al, , 2012Palazzo et al, 2011). This result might be attributed to the ability of polyphenols to neutralize free-radical production at the stage of propagation of the chain reaction (Funes et al, 2009) or to inhibit the activity of prooxidant enzymes responsible for their production, thus protecting both LDL lipids and the α-tocopherol of LDL from the attack of radicals (Cos et al, 2002), and promoting regeneration of the radical forms of α-tocopherol (Zhou et al, 2005).…”
Section: Blood Parameterssupporting
confidence: 88%
“…Improvement of lipid profiles was observed in our earlier work on Italian hares (Lepus corsicanus), rabbits, and dairy ewes intensively reared and fed diets supplemented with water-soluble extracts of Verbenaceae (Lippia spp.) leaves (Casamassima et al, , 2012Palazzo et al, 2011). In particular, a decrease of total cholesterol and triglycerides and an increase of HDL-C was found.…”
Section: Blood Parametersmentioning
confidence: 82%
See 2 more Smart Citations
“…The better oxidative profile was highlighted by a significant decrease in the concentration of thiobarbituric acid reactive substances (TBARS) and reactive oxygen metabolites (ROMs) and, in lambs, also by a marked increase in blood concentrations of vitamins E and A. In similar experiments, by feeding pairs of Italian hares (Lepus corsicanus) a concentrate supplemented with verbascoside, Palazzo et al (2011) found an increase in high density lipoprotein cholesterol (HDL-cholesterol) and a significant reduction in blood triglycerides, total cholesterol, and bilirubin. The authors also reported an improvement in oxidative plasma stability resulting in an increased content of vitamins A and E and a decrease in the concentrations of TBARS and ROMs.…”
mentioning
confidence: 99%